SrMGe2O6 (M = Mn, Co): a family of pyroxene compounds displaying multiferroicity. Issue 19 (13th April 2016) - Ding, Lei; Colin, Claire V.; Darie, Céline; Bordet, Pierre
Abstract : The Sr-based pyroxene compounds SrMGe2 O6 (M = Mn, Co) have been synthesized and their structural and magnetoelectric properties have been investigated. SrMnGe2 O6 is a multiferroic with cycloidal spin configuration. Abstract : The family of Sr-based pyroxene compounds SrMGe2 O6 (M = Mn, Co) has been synthesized and investigated by means of X-ray single crystal and powder diffraction, neutron diffraction, magnetic susceptibility and heat capacity measurements. Both SrMnGe2 O6 and SrCoGe2 O6 crystallize with monoclinic C 2/ c symmetry. Magnetoelectric and neutron powder diffraction measurements indicate that SrMnGe2 O6 is a multiferroic of spin origin with a magnetic order characterized by a cycloidal spin configuration below 4.5 K, while SrCoGe2 O6 displays a commensurate magnetic structure below 10 K with space group P c 21 / c . The comparison between Sr- and Ca-based pyroxenes from structural and magnetic viewpoints allows us to identify the relevant parameters for the magnetic ground states and magnetoelectric properties.